Digital transformation in higher education: Global trends and future research direction - Harjanto Prabowo; Agustinus Bandur (Journal of Innovation in Business and Economics, 2021)
This paper explores global trends and future research direction of digital transformation in Higher Education Institutions (HEIs);  A bibliometric study was conducted with a total of 125 Scopus-indexed articles in the areas of Arts and humanities; business, management, accounting; economics, econometrics and finances; and social sciences. Analysis results indicate a diversity of publications in the last decade, including various research designs, article types, and geographical distribution of the studies. Qualitative content analysis reveals the significant focuses for future studies, including HEIs digital transformation framework, business model, and leadership capability. This paper serves as a point of departure for future research in higher education digital transformation.